Think Pair Share Integrated with Make a Match: A Cooperative Learning Strategy to Improve Vocabulary Mastery among Young EFL Learners - Stella Siwalette; Nursalim (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
Vocabulary is essential for developing language proficiency, particularly among young EFL learners who rely on vocabulary knowledge to support their reading, writing, listening, and speaking skills. However, many elementary students in Indonesia struggle with vocabulary retention and application due to traditional, teacher-centered instruction and limited engagement. This study examines the effectiveness of integrating two cooperative learning strategies Think Pair Share (TPS) and Make a Match (MaM) to improve vocabulary mastery among fifth-grade students at SD YPPK Kristus Raja I Kampung Baru. Using a pre-experimental one-group pretest-posttest design, the research involved 18 purposively selected students from a single fifth-grade class. A 20-item vocabulary matching test focused on basic English nouns and verbs was administered before and after the intervention. The instructional treatment was implemented over four sessions, combining structured peer discussion using TPS and interactive word-matching activities using MaM. The data were analyzed using descriptive statistics and a paired sample t-test with SPSS. The results revealed a statistically significant improvement in students’ vocabulary scores (p = 0.000), with an average gain of over 30 points from pretest to posttest. Most students moved from the “poor” and “fair” categories to “good” and “very good,” indicating substantial vocabulary growth. The findings suggest that the integration of TPS and MaM not only enhances vocabulary comprehension and retention but also promotes higher student engagement and confidence in using new words. This study provides empirical evidence that interactive, cooperative learning strategies can be highly effective in supporting vocabulary development among young EFL learners. Teachers are encouraged to implement these methods to create more student-centered, engaging vocabulary instruction. Further studies with larger samples and varied contexts are recommended to validate and expand on these results.